ENTRY POINTS AND TRAILHEADS: PONDERING THE HISTORY AND FUTURE OF THE WILLIAM P. CLEMENTS CENTER FOR SOUTHWEST STUDIES. - GRAYBILL, ANDREW R. (Western Historical Quarterly)
Since its establishment in the fall of 1996, the William P. Clements Center for Southwest Studies at Southern Methodist University in Dallas, Texas, has served as a key incubator of first-rate scholarship on Texas and the transnational U.S.-Mexico borderlands. Although its visionary founding director, David J. Weber, died in August 2010 (his final article appears in this issue of western Historical Quarterly), the core mission of the center remains the same. As Weber's successor, I describe the annual operations of the Clements Center while touching on some of my own ideas about the future of this vital academic institute.